Student-Teacher Strategies And Practices Toward Effective Classroom Management In Teaching And Learning English At Senior High School In Jambi City - Agustian (Universitas Adiwangsa Jambi, 2022)
The purpose o of this study is to describe how an English student- teacher Manages effective classes in teaching and learning English at Senior High School in Jambi City. This study is focused to find out the strategies of classes management an effective classroom especially Eglish subject in class XI IPS and to find out the ways the English student-teacher practices in teaching for the four skills such as; listening, reading, writing and speaking.This study was a descriptive qualitative research conducted in class XI IPS at Senior High School in Jambi City, which consisted of 34 students. The researcher held interviewer and observation were applied in data collection. The result showed that the student- teacher was able to know and applied the effective management in teaching and learning for the four skills in English such as, listening, reading, writing and speaking.it seem that student-teacher had applied the aspects of the effective classroom management in evert teaching English process in teaching listening, reading, writing and speaking skills well.